Comparing three theories of participation in pro-environmental, collaborative governance networks. (15th June 2019) - Barrutia, Jose M.; Echebarria, Carmen
Abstract: While several different theories have been proposed to explain why organizations participate in networks, there is no consensus on which motivations are most important. The aim of this research is to better understand attitudes of participants towards the networks of which they are members. We propose and test a model in the context of pro-environmental, collaborative governance networks. The model is based on three theories (i.e., Resource Dependence, Social Exchange, and Social Identity theories), which are represented by three variables (i.e., network resources, image enhancement and identification, respectively). As expected, the three variables are shown to have explanatory capacity, and interestingly, their co-presence generates synergistic effects. When comparing the relative explanatory power of these variables we find that Social Identity Theory, represented by identification, has the strongest influence on participation attitude in the form of an increasing returns effect. When network participants identify with their pro-environmental networks, a powerful motivational mechanism emerges: participants merge their own personal identity with the identity of the network, and their self-esteem is affected by the achievements of the network. Identification goes a long way in explaining participation attitudes, and deserves a major role in collaborative governance and collective action research. Highlights: Testing attitudes of participants towards pro-environmental networks. Network resources have a positive effect on participation attitude. Image enhancement has a positive effect on participation attitude. Identification has the strongest influence on participation attitude. Resources, image and identification generate synergistic effects.